Aqueous Dissolution of Phenanthrene from Loess Soil using Triton X-100 and Sodium Dodecylbenzene Sulfonate - Zhao, Baowei; Jiang, Bin (Asian Journal of Chemistry, 2011)
Surfactant-enhanced remediation is a feasible technology for the clean-up of hydrophobic organic contaminants in subsurface, in which enhanced desorption of hydrophobic organic contaminants from soil medium plays a key role in remediation efficiency. In this paper, solubilization and washing of phenanthrene from loess by Triton X-100 (TX100), sodium dodecylbenzene sulfonate (SDBS) and their mixture (TX100-SDBS) solutions were tested and compared. The effects of inorganic salts (Na+, Ca2+ and Mg2+) on solubilization and adsorption of surfactants onto loess were investigated simultaneously. It was found that the solubilization capacities of surfactants were in the order TX100 > 3:1 TX100-SDBS > 1:1 TX100-SDBS > 1:3 TX100-SDBS > SDBS and the solubilization ratios (SR) of these surfactants were 0.021, 0.018, 0.014, 0.009 and 0.002, respectively. A synergistic solubilization was obviously found in mixed TX100-SDBS systems. An appropriate addition of inorganic salts could enhance solubilization and the mixed TX100- SDBS could endure harder water than single SDBS did. The adsorption of TX100 onto loess could be reduced by anionic surfactant. The soil washing experiment demonstrated a high desorption of phenanthrene from spiked loess soil by 3:1 and 1:1 TX100-SDBS, compared with by single TX100 or SDBS. The results showed mixed surfactant could be an attractive alternative to single ones in the remediation of the contaminated loess soils.